Ethnoecology: The traditional landscape of Osing Tribe in Banyuwangi, Indonesia - BUDI PRASETYO; TATIK CHIKMAWATI; EKO BAROTO WALUJO; ERVIZAL AMZU (Society for Indonesian Biodiversity, 2018)
Prasetyo B, Chikmawati T, Walujo EB, Amzu E. 2018. Ethnoecology: The traditional landscape of Osing Tribe in Banyuwangi, Indonesia. Biodiversitas 19: 2003-2009. There is a concern that the decreasing area of Osing tribe in Banyuwangi may cause the decline of the farming culture that has been rooted in their daily lives. This research aimed to analyze the traditional knowledge of Osing tribe in the management and utilization of landscape units generated from farming activities and the benefit assessment of landscape units based on gender perception. The research used explorative method with emic and ethic approaches. The importance of each landscape element is assessed through MLA (Multidisciplinary Landscape Assessment) by scoring with Pebble Distribution Method (PDM) in Focus Group Discussion (FGD). The respondents consisted of females and males with three age categories: 11-17 years, 18-45 years, and ? 46 years. The results of PDM showed that the Osing tribes in the three villages of study sites considered their yards as the most important landscape unit in their lives (PDM = 42.82), followed by paddy field (PDM = 26.05), garden (PDM = 16.12), and finally field (PDM = 15.01). Based on gender perception, a house with a yard had higher importance (PDM = 45.09) in female’s perception than in male’s (PDM = 40.55). Three canopy strata or layerswere found in village landscapes, namely yard, paddy field, garden, and field.